Associations of blood biomarkers and structural changes in atherosclerosis in the Longitudinal study of adult heath (Elsa-Brasil): emphasis on pre-and postmenopausal women - Fonseca, Marília Izar Helfenstein (2021)
Background: Cardiovascular disease is the leading cause of morbidity and mortality in women worldwide. Cardiovascular risk prediction is incomplete and new markers may help in the early identification of atherosclerosis. Brazilian epidemiological data in women are scarce. Objectives: To review the impact of menopause and diabetes on lipids, lipoprotein subfractions and cardiovascular risk; evaluate cardiometabolic risk in women from the ELSA-Brasil, as well as associations of blood biomarkers [lipoprotein subfractions, insulin resistance index (HOMA-IR) and branched-chain amino acids (BCAA)] and structural changes of atherosclerosis [presence of calcium in the coronary arteries (CAC)] according to age and menopausal status. Methods: Cross-sectional baseline analyzes of 2,258 female participants from the São Paulo site of the ELSA-Brasil, stratified by age and menopausal status, with specific sample and eligibility criteria for each paper. Descriptive statistics, between-group comparisons and multiple regression were performed according to the nature and distribution of the variables for each paper. Results: Paper 1: Literature revision enabled conclusions regarding the association of menopause and diabetes with a worse lipid profile, including hypertriglyceridemia, lower levels of HDL-c and HDL2-c, higher levels of HDL3-c and small dense LDL-c. Postmenopausal diabetic women consist of the highest cardiovascular risk level. Paper 2: Comparing pre- and postmenopausal women categorized according to time since menopause [menopausal duration <2 years, 2-5.9 years, 6-9.9 years or ≥ 10 years (n=1916)], postmenopausal women had a worse lipid and lipoprotein subfraction profile and duration of menopause <2 years was independently associated with remnant lipoprotein cholesterol (TRL-c) [7.21 mg/dL (95% CI 3.5910.84)] and smaller denser VLDL3-c [2.43 mg/dL (95%CI 1.023.83)], but no associations of menopausal categories with HDL-c or LDL-c subfractions were found, when taking premenopausal women as reference. Paper 3: Comparing premenopausal ≤ or >45 years and postmenopausal women (n=2047), postmenopausal ones had the worst cardiometabolic risk profile. CAC>0 was found to be associated with TRL-c and dense LDL-c, but not with BCAA levels nor HOMA-IR. Postmenopausal women were about twice as likely to have CAC>0 than younger premenopausal ones [OR 2.37 (95%CI 1.17-4.81)]. Discussion: Our findings suggest that natural menopause is associated with changes in lipoprotein fractions and subfractions (especially in the first 2 years post-menopause) and with calcium deposition in the coronary arteries independently of age and other risk factors, but not with BCAA nor HOMA-IR. Deep investigation on lipid profile and other biomarkers in women approaching to menopause is needed in order to identify cardiovascular risk, prevent cardiovascular outcomes and provide better health conditions.